Penerapan Metode Muhadatsah dalam Pembelajaran Bahasa Arab Guna Peningkatan Kemahiran Berbicara Siswa Kelas VIII MTs Muhammadiyah Kota Bengkulu - Eva Setia (Yayasan Darussalam Bengkulu, 2024)
This study aims to describe the implementation of the Muhadatsah Method in Arabic language learning and its impact on improving the maharotul kalam of class VIII students at MTs Muhammadiyah Kota Bengkulu. The type of research used is descriptive qualitative, with data collection techniques through interviews, observations, and documentation. The main informants in this study were teachers and students. The results of the study indicate that the implementation of the Muhadatsah Method has succeeded in improving students' speaking ability in Arabic. Teachers implement this method well, creating an interactive and communicative learning atmosphere. Students show high enthusiasm in following the learning process and experience significant improvements in their speaking abilities. Classroom observations reveal that students are more active in participating in discussions and speaking exercises, and are able to express their opinions more confidently. Documentation shows an increase in scores in the evaluation conducted after the implementation of the method. Thus, this study concludes that the Muhadatsah Method is effective in improving students' maharotul kalam, and is expected to be widely applied to advance Arabic language learning at other levels of education. This study contributes to the development of innovative teaching methods and improves the quality of Arabic language education in Indonesia.